LIGHT FROM BELOW - Samuelsen, Geir Harald (Design/Arts/Culture, 2023)
The light is shining from the ground, minutes after the sun has set. The Fontainebleau sand is glowing with a mysterious light from below. I prepare for the camera to capture it. If it does, it will capture the disappearing sun shining in the bright surface of the sand.